EXTENT OF TEACHER PREPAREDNESS AND CAPACITY TO IMPLEMENT INFORMATION AND COMMUNICATION TECHNOLOGIES IN THE NEPAD E-SCHOOLS, KENYA - Mogeni, Mobisa Jackson; Ondigi, Samson R.; Mugo, Bernard C. (African Journal of Education and Practice, 2020)
Purpose: The purpose of this study was to determine the extent to which teachers and principals are prepared and capacitated to implement ICTs in the NEPAD e-Schools, Kenya. Methodology: This study adopted a descriptive survey design. Both quantitative and qualitative data were collected. The target population for the study were all principals and 256 teachers from 6 model e-Schools. Sampling was done employing a mixture of methods. Stratified sampling was used to pick schools, while purposive sampling was used to pick principals and teachers. Five principals and 110 teachers were sampled. Data was collected using questionnaire for teachers, and structured interview for principals. The collected data was coded, run for descriptive analysis; including frequencies, percentages, measures of central tendency and measures of variability/spread, and presented with the aid of appropriate notes, frequency tables, percentages, charts and figures. Findings: The study established that despite most teachers and principals having been trained, they had not been sufficiently empowered towards effectively and successfully applying ICTs. Moreover, majority of the untrained teachers and principal had not trained because no training had occurred since they joined the schools. However, despite their status, most teachers believed they could still perform some tasks involving ICTs. Most trained teachers and principals needed to be trained, retrained and/or trained further on several skills, especially in the preparation and use of multimedia instructional tools, and on-line research and communication. The study concluded that most teachers and principals may be willing to apply ICTs but are limited by the nature and extent of their empowerment. Moreover, ICTs application programmes are likely to succeed better if they employ regular, on-going training. Unique contribution to theory, practice and policy: The study could inform education planners and trainers about necessary adjustments to future pre-service and in-service teacher training programmes involving application of ICTs. It would also contribute to the body of knowledge in educational technology, which might inform theory and practice in ICTs integration. It could also inform the development of best practices in the application and integration of ICTs in instruction.